COMPARISON OF LEADERSHIP AT STIKES BUDI LUHUR AND MAHSA UNIVERSITY IN EFFORTS TO IMPROVE THE QUALITY OF HEALTH EDUCATION - Waska Warta; Puteri Norliana Binti Megat Ramli, Muzahir Bin Mohamad; Damai Yanti, Yosi Oktri, Selvia Ruyatus Saefullah (Adisam Publisher, 2024)
This study aims to compare the leadership styles at STIKES Budi Luhur Cimahi and Mahsa University Malaysia in their efforts to improve the quality of health education. Both STIKES Budi Luhur Cimahi and Mahsa University Malaysia have shown a strong commitment to enhancing educational quality by implementing different yet equally effective leadership styles. STIKES Budi Luhur Cimahi emphasizes developing a curriculum that meets the needs of the health industry, along with the development of soft skills and religious character. On the other hand, Mahsa University Malaysia focuses on improving the quality of faculty through regular training, upgrading facilities and infrastructure, and utilizing information and communication technology in the learning process. The study finds that despite differences in leadership approaches, both institutions successfully create a conducive, innovative, and competitive learning environment. These findings are expected to provide valuable insights for leaders of other higher education health institutions in formulating effective leadership strategies to enhance educational quality.